2013
DOI: 10.1099/jmm.0.055491-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and evolutionary analysis of HPV16 E6 and E7 genes in Greek women

Abstract: Human papillomavirus type 16 (HPV16) non-European variants have been associated with persistent infection and cervical cancer development, while the L83V variant of the E6 gene has been correlated with the progression of cervical malignancy. The present study investigated the presence of the HPV16 L83V variant in Greek women. Molecular evolutionary analysis of the HPV16 E6 and E7 oncogenes was conducted in order to estimate the evolution of the HPV16 genome in the Greek population. The E6 L83V variant was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
(81 reference statements)
1
9
0
Order By: Relevance
“…Similar results in women with cervical cancer were observed in Slovenia (62.5%) (Vrtačnik Bokal et al, 2010) but a lower frequency (49%) of EUR 350G was reported across Europe in a recent meta-analysis (Tornesello et al, 2011). In our research the incidence of EUR-350G variant in the LSIL group was similar to the results of studies in Greece (64%) and in Italy (65%) but higher than in England (41%) (Tsakogiannis et al, 2013;Burroni et al, 2013;Marongiu et al, 2014). In a recent study, the International Agency for Research on Cancer (IARC) HPV Variant Study Group revealed, by examining 1121 HPV16 positive cervical cancer cases and 400 HPV16 positive controls worldwide, that E-350G is associated with an increased risk of developing cervical cancer in South and Central America but not in Europe nor Central Asia (Cornet et al, 2013a).…”
Section: Discussionsupporting
confidence: 90%
“…Similar results in women with cervical cancer were observed in Slovenia (62.5%) (Vrtačnik Bokal et al, 2010) but a lower frequency (49%) of EUR 350G was reported across Europe in a recent meta-analysis (Tornesello et al, 2011). In our research the incidence of EUR-350G variant in the LSIL group was similar to the results of studies in Greece (64%) and in Italy (65%) but higher than in England (41%) (Tsakogiannis et al, 2013;Burroni et al, 2013;Marongiu et al, 2014). In a recent study, the International Agency for Research on Cancer (IARC) HPV Variant Study Group revealed, by examining 1121 HPV16 positive cervical cancer cases and 400 HPV16 positive controls worldwide, that E-350G is associated with an increased risk of developing cervical cancer in South and Central America but not in Europe nor Central Asia (Cornet et al, 2013a).…”
Section: Discussionsupporting
confidence: 90%
“…According to our findings, the most frequently disrupted site was located in the E2 hinge region (from nucleotide 3172 to 3649), while the most prevalent site of disruption within the E1 gene was located between nucleotides 1059 and 1323. Moreover, nucleotide analysis of the E1 and E2 genes in the same cervical samples, which were derived from Greek women, revealed that the region between nucleotides 3172 and 3649 (E2 gene) and the region between nucleotides 1059 and 1323 (E1 gene) are conserved among distinct HPV16 isolates that are circulating in the Greek population (Tsakogiannis et al , 2012, 2013, 2014). Taking these data into consideration, we targeted the E2 domain between nucleotides 3243 and 3539, and the E1 domain between nucleotides 1059 and 1323, through RT-PCR, in order to assign the copy numbers of the E2 and E1 genes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, a total of 61 precancerous cervical samples and 8 cervical cancer cases associated with HPV16 infection were investigated in order to study the physical status of the HPV16 genome through quantitative RT-PCR and E2/E6 and E1/E6 ratio values analysis. However, in order to achieve more reliable results, the selection of E1, E2 and E6 targets was based on the most frequently disrupted sites of the E1 and E2 genes, and according to the most conserved E6 regions among the same HPV16 isolates, which were recently reported by our group (Tsakogiannis et al , 2012, 2013, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The E7 gene was also analyzed in order to examine sequence variations that might be associated with the E1‐1374^63nt duplication. Thus, the E6–E7 region was amplified using the primer set HPV16 41/HPV16 757 as has been recently reported [Tsakogiannis et al, ].…”
Section: Methodsmentioning
confidence: 99%